Leadership in Islamic Education Institution - Supriadi, Supriadi (AT-TALIM, 2014)
Education institution may not be separated by social system. It can be formal and informal education. A formal education institution such as school, Islamic school or Islamic boarding school is in social environment and bringing a basic value and law from its institution. Meanwhile, Islamic education institution is believed as tool to reach the aim of education. The aim of education is hard to reach if there is no leadership in it.Â Copyright Â© 2014 by Al-Talim All right reserved